Synchronization for a Class of Fractional-Order Hyperchaotic System and Its Application - Wen Tan; Feng Ling Jiang; Chuang Xia Huang; Lan Zhou (Journal of Applied Mathematics)
A new controller design method is proposed to synchronize the fractional-order hyperchaotic system through the stability theory of fractional calculus; the synchronization between two identical fractional-order Chen hyperchaotic systems is realized by designing only two suitable controllers in the response system. Furthermore, this control scheme can be used in secure communication via the technology of chaotic masking using the complex nonperiodic information as trial message, and the useful information can be recovered at the receiver. Numerical simulations coincide with the theoretical analysis.